Penerapan Media YouTube Dalam Pembelajaran Menganalisis Berita Palsu Kelas VII SMP Negeri 10 Kota Jambi Tahun 2023/2024 - Rasdawita, Rasdawita; Haliza, Finta; Rahmawati, Rahmawati (Universitas Nahdlatul Ulama Blitar, 2024)
YouTube media can increase students' interest and motivation to learn, can foster an attentive attitude, creativity, as well as students' cognitive and psychomotor abilities to develop their reasoning from what they see and hear. This type of research is classroom action research with presentation of qualitative descriptive data and quantitative data. Qualitative data was obtained from observation sheets for each action implementation (learning process), and quantitative data was obtained from the final test of each cycle. Class VII students of SMP Negeri 10 Jambi City. Meanwhile, the subjects in this research were class VII students at SMP Negeri 10 Jambi City for the 2023/2024 academic year. Of the 28 students, there were 25 students who succeeded in analyzing the truth of 10 news stories presented via YouTube. It can be concluded that their analytical skills were quite good overall.